2020
DOI: 10.3747/co.27.6399
|View full text |Cite
|
Sign up to set email alerts
|

A Catalyst for Transforming Health Systems and Person-Centred Care: Canadian National Position Statement on Patient-Reported Outcomes

Abstract: Background Patient-reported outcomes (pros) are essential to capture the patient’s perspective and to influence care. Although pros and pro measures are known to have many important benefits, they are not consistently being used and there is there no Canadian pros oversight. The Position Statement presented here is the first step toward supporting the implementation of pros in the Canadian health care setting. Methods The Canadian pros National Steering Committee drafted position statements, which were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 45 publications
1
18
0
1
Order By: Relevance
“…The priorities identified in the present study are consistent with those identified by others, notably, the Canadian position statement [24]; however, the Canadian recommendations were derived from health professionals or academic researchers and were not ranked in terms of prioritisation of which items to consider first.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The priorities identified in the present study are consistent with those identified by others, notably, the Canadian position statement [24]; however, the Canadian recommendations were derived from health professionals or academic researchers and were not ranked in terms of prioritisation of which items to consider first.…”
Section: Discussionsupporting
confidence: 85%
“…Our targeted review search identified one position statement on how to best integrate PROs into clinical practice [24], several scoping/systematic/pooled reviews that discussed implementation of PROs [6,[25][26][27][28][29][30][31], and five methodological and research articles that discussed using implementation approaches to implement and evaluate PRO use in clinical practice [5,9,[32][33][34]. These sources led to the development of 71 suggested statements (Appendix F).…”
Section: Priority Statement Generationmentioning
confidence: 99%
“…We recommend that organizations identify a local expert, establish clinical champions,and/or care a working group to set realistic and consensus-driven expectations for the successful implementation of PROs. [ 30 , 31 ] For example, institutions that are still in the early phases of implementation can focus on monitoring and adjusting algorithms to optimize the likelihood of success. To address the issues of limited staff support and resources, they may also consider adopting a staggered or waved rollout using principles of implementation science.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence demonstrates that capturing qol and symptoms in a real-world context improves symptom control, patient satisfaction 38,39 , and health-related quality of life 40 ; is associated with increased survival duration 36,37,[41][42][43] ; and is becoming more common in real-world clinical settings 44,45 . In recognition of those benefits, a group of Canadian experts and stakeholders, including the Colorectal Cancer Resource and Action Network, developed and published a position statement supporting the greater use of patient-reported outcomes in Canadian health care and research contexts 46 .…”
Section: Discussionmentioning
confidence: 99%